2016
DOI: 10.1016/j.bbrc.2016.06.098
|View full text |Cite
|
Sign up to set email alerts
|

Transferring the C-terminus of the chemokine CCL21 to CCL19 confers enhanced heparin binding

Abstract: Chemokines direct the migration of cells during various immune processes and are involved in many disease states. For example, CCL19 and CCL21, through activation of the CCR7 receptor, recruit dendritic cells and naïve T-cells to the secondary lymphoid organs aiding in balancing immune response and tolerance. However, CCL19 and CCL21 can also direct the metastasis of CCR7 expressing cancers. Chemokine binding to glycosaminoglycans, such as heparin, is as important to chemokine function as receptor activation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…30 Here we show that transfer of the CCL21-tail to CCL19 (CCL19 CCL21-tail ) does not negatively affect CCL19's ability to induce chemotaxis in human DCs, despite the increased surface binding of this chimera to DC surfaces, ruling out that binding to the cell surface per se interferes with chemotaxis. Our finding is consistent with a study by Barmore et al 31 that reveals increased heparin binding by the same chimera, CCL19 CCL21-tail compared to CCL19, which demonstrates that the basic C-terminal tail of CCL21 is enough to confer high GAG affinity. Interestingly, we show here, that CCR7 internalization driven by CCL19 CCL21-tail decreased compared to CCL19 but is not as low as for CCL21, indicating that high GAG affinity somehow has an effect on the ability of CCR7 to internalize.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…30 Here we show that transfer of the CCL21-tail to CCL19 (CCL19 CCL21-tail ) does not negatively affect CCL19's ability to induce chemotaxis in human DCs, despite the increased surface binding of this chimera to DC surfaces, ruling out that binding to the cell surface per se interferes with chemotaxis. Our finding is consistent with a study by Barmore et al 31 that reveals increased heparin binding by the same chimera, CCL19 CCL21-tail compared to CCL19, which demonstrates that the basic C-terminal tail of CCL21 is enough to confer high GAG affinity. Interestingly, we show here, that CCR7 internalization driven by CCL19 CCL21-tail decreased compared to CCL19 but is not as low as for CCL21, indicating that high GAG affinity somehow has an effect on the ability of CCR7 to internalize.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, CCL19 and CCL21 only display 32% sequence identity and differ in length with CCL21 encoding a 37 amino acid long C‐terminal tail extension that is lacking in CCL19, giving rise to significant differences in GAG affinity . We have previously shown that CCL21 is captured on the surface of human monocyte derived DCs (moDCs) to a much higher extent than CCL19, a characteristic that is dependent on the basic C‐terminal tail of CCL21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, full-length CCL21 induced integrin-dependent dendritic cell spreading, polarization and haptotactic movement, whereas CCL21 missing the positively charged COOH-terminus induced non-adhesive and integrin-independent directional migration (218). Interestingly, linking the COOH-terminal tail of CCL21 to the related CCR7 ligand CCL19 enhanced its affinity for heparin (219).…”
Section: Consequences Of Ccl19 and Ccl21 Binding To Glycosaminoglycansmentioning
confidence: 99%
“…For example, only CCL19 activation of CCR7 results in receptor internalization and desensitization [ 21 , 42 ]. A truncated version of CCL21, in which CCL21’s unique, glycosaminoglycan-binding C-terminal tail has been proteolytically removed by plasmin, also results in signaling that is unique compared to CCL19 and full length CCL21 [ 43 , 44 , 45 , 46 ]. This ligand bias likely results from different CCR7 conformations in the presence of CCL19 and either full length or truncated CCL21 [ 43 ], but tyrosine sulfation in CCR7 could also be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%